Evaluasi Kinerja Sistem Informasi Kepegawaian pada Dinas Kependudukan dan Catatan Sipil Salatiga Menggunakan COBIT 5 - Zelafehad Mega Naskay; Agustinus Fritz Wijaya (Jurnal Bina Komputer, 2020)
The information system used must be balanced with the correct processing to support business processes and become an operational supporter of the organization. In caryyng out business process there are several factors that must be considered by the company, not only focusing on the use of information technology that supports business processes, but the company must be able to focus on maintenance, monitoring and management. Therefore, researchers use the Monitor, Evaluate and Assess domains. The purpose of this study is to measure the level of information technology maturity at Dinas Kependudukan dan Catatan Sipil Kota Salatiga. The research methodology is a qualitative method, by collecting data and interviews with informants. The results of this study are to determine the level of maturity of Dinas Kependudukan dan Catatan Sipil Kota Salatiga and provide recommendations, so that the application of information technology can be better.